New Records of Spiders (Arachnida: Araneae) from Sinop Province, Turkey, Including an Annotated List of Species - Eti̇rli̇, Esra; Koç, Halil; Sancak, Zafer (Kastamonu University, 2019)
Aim of study: This study was conducted to determine the biological richness of spiders from Sinop province, Turkey.Area of study: The studies were carried out on between 41° 12' and 42° 6' northern latitudes and 34° 14' and 35° 26' east longitudes within the Sinop province borders.Material and Methods: Spiders were collected from 2009 to 2015 using four collection methods: using sweep netting, tree beating, active searching and pitfall trapping.Main results: A total of 1766 specimens were collected that represented by 31 families, 133 genera and 200 species. The most diverse families collected are the Salticidae (29 spp.), Theridiidae (29 spp.) and Gnaphosidae (21 spp.). According to previous studies and this work, 31 families, 139 genera, 212 species of spiders are present in Sinop province, of which 192 species are recorded for the first time. Research highlights: Furthermore, one genus (Theridula Emerton 1882) and three species, namely Asagena meridionalis Kulczyński 1894, Theridion boesenbergi Strand 1904 and Theridula gonygaster (Simon 1873), are new records for Turkey, and are provided with illustrations. Here, we provide the first annotated checklist of the spider species of Sinop province.
Keywords: Sinop; Fauna; Tür zenginliği; Sinop; Araneae; Fauna; yeni kayıt; kontrol listesi; Species richness; Sinop; Araneae; Fauna; new records; checklist; Araneae; new records; checklist; Species richness